Антропологічні виміри природи конфліктів в публічному управлінні - Вороніна, Юлія Євгенівна; Воронина, Юлия Евгеньевна; Voronina, Yuliia (My University, 2019)
UK: Статтю присвячено проблемам виникнення конфліктних ситуацій між гілками влади, різними політичними силами та громадськістю, окремими політичними лідерами та суспільством, місцевою та центральною владою, між владою та народом. Саме вміння толерантно і з увагою до всіх сторін конфлікту вирішувати такі проблемні ситуації є важливим елементом, способом гуманізації суспільної свідомості, свід-ченням відповідальності, зрілості й демократичної готовності громадян. EN: Modern society is a complex, dynamic, holistic system. Rational understanding of the causes of its occurrence, patterns of development and functioning cannot be complete and comprehensive without a deep penetration into the essence and content of the contradictions inherent in this society. The purpose of the article is to investigate the problems of conflict management, prevent destructive conflicts as destabilizing public relations, de-stroy relations between its members, and contribute to the adequate and effective resolution of constructive conflicts, which, unlike destructive conversions, lead to such positive consequences, that unite the collective, society, etc. Research results. Each political system adapts its mechanism of conflict resolution to the relevant conditions that have emerged in society and the outside world, the mentality of the people, the state of public consciousness, and urgent administrative needs. It is mediated by the ideological precepts of the ruling class, the dominant mode of production, the level of openness of society, the nature of social ties (plastic or rigid), the level of legitimacy of the regime, and so on. However, the ability to tolerate and respect all sides of the conflict in a tolerant manner and in such situations is an important element, a way of humanizing the public consciousness, a testament to citizens' responsibility, maturity and democratic readiness. Conclusions. Modern Ukrainian state formation is accompanied by conflicts between branches of power, different political forces and the public, individual political leaders and society, local and central authorities, between the au-thorities and the people. Conflict-free public administration is impossible, so the need to prevent and prevent the devel-opment of destructive conflicts, which are mostly subjective in nature, and to resolve objectively contradictions of pub-lic administration in a constructive way, requires scientific understanding and development of appropriate mechanisms that would enable them to diagnose them. the earliest stage.
Anthropological measurements of the nature of conflict in public administration
Keywords: конфлікт; управління конфліктами; конструктивні конфлікти; деструктивні конфлікти; інституціоналізація конфлікту; міжособистісні конфлікти; conflict; conflict management; constructive conflicts; destructive conflicts; institutionalization of conflict; interpersonal conflicts